Drug Utilization review of monitored parenteral antimicrobials in a tertiary care private hospital in Cebu City - So, Jan Steven P.; Capule, Francis (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Infectious diseases remain as principal determinants of morbidity and mortality in our country due to the advent of drug resistance. Major drivers for AMR may be attributed to indiscriminate prescribing and consumption. AMS programs are established to mitigate the adverse consequences of AMR. Drug use evaluation in hospitals ensures provision of rational medication therapy to patients.

Infectious diseases remain as principal determinants of morbidity and mortality in our country due to the advent of drug resistance. Major drivers for AMR may be attributed to indiscriminate prescribing and consumption. AMS programs are established to mitigate the adverse consequences of AMR. Drug use evaluation in hospitals ensures provision of rational medication therapy to patients.

This study was conducted to review the utilization of monitored parenteral antimicrobials in a tertiary care private hospital in Cebu City. A retrospective review of charts involved patients admitted during 2019. 821 patient charts were included in the study.

Majority of the patients were 61-65 years old (11%) and 52% were females. Almost all availed of the medical service (90%). General IM practitioners (28%) primarily prescribed these agents for CAP-MR (39%). They were mostly for empirical treatment (94%) and given for an average of 5.73 days. Specifically, piperacillin-tazobactam 4.5 g q8h (39%) was frequently prescribed. E. coli (19%) was often isolated in cultures. All the microorganisms isolated were most resistant to ampicillin (81%) and most susceptible to colistin (100%).

There was one (0.1%) and two (0.2% cases of adverse drug reaction and contraindications, respectively. Therapeutic duplication was also observed in 5% of the cases. Moreover, 39% of cases had drug-drug interactions. Piperacillin-tazobactam had the highest consumption at 79.50 DDDs/1,000-PDs. 12% of cases were inappropriate based on the justification indicator. As for the critical indicators, duration of therapy (78%) was the main reason of inappropriateness. Potential cumulative cost savings of P2,728,387.44 could have been achieved.

In conclusion, consumption of piperacillin-tazobactam was relatively high. Physicians seldom prescribe monitored antimicrobials as recommended by the DOH NAG. Drug therapy related problems may have been prevented through avoidance of certain interacting medications. Adherence to the established guidelines could have resulted in cost savings for the patients.
Thesis (Master of Science in Pharmacy)--University of the Philippines Manila, January 2023.
Keywords: Infectious diseases; Drug Resistance, Microbial; Antimicrobial Stewardship; Drug Resistance, Bacterial; Antimicrobial agents; Drug Therapy, Combination; Piperacillin-Tazobactam.; AMR (Antimicrobial Resistance).; Inappropriate Prescribing; Critical Indicators